Probes and techniques used in active and the hypoxia-based dormant state of an antitubercular drug screening assay - Amar Yeware; Shamim Akhtar; Dhiman Sarkar (Elsevier, 2022)
Current antitubercular drug therapy requires more than six months and is unable to kill latent or dormant forms of tuberculosis. Thus, it is a need of new drug therapy to fight against dormant tuberculosis. However, the major obstacle in the development of novel drugs for dormant tuberculosis is the lack of relevant screening systems and using reliable probes to measure growth inhibition. Until now, several probes used in active state assays are significantly determining the inhibitory effect against the active state of mycobacteria. The dormant condition assays are based on hypoxia-derived dormancy which include resazurin reduction assay, nitrite reductase assay, XTT reduction menadione assay and low oxygen recovery assay. Major probes used in those assays are colorimetric/fluorescent dyes, enzymatic activity, and reporter genes include luciferase and fluorescent proteins. Although these dormant assays are based on hypoxia-induced features and difficult to maintain for a longer duration. Also, they further complicated by growth detection and pursuit of high throughput screening criteria. Here we reviewed complications of probes and assay techniques used for anti-dormant drug screening programs of tuberculosis. This will provide the knowledge to design better alternative drug screening method for the anti-dormant form of tuberculosis.